Herbal wealth of western ghats Agasthyamalai: a pictorial & herbal guide - India. Ministry of Ayush. Central Council for Research in Ayurvedic Sciences (CCRAS) (New Delhi: CCRAS, 2016)
The book provides an overview of various facts of the herbal Wealth of Agasthyamalai hill region. It assimilates of information containing numerous published as well as unpublished data, herbarium, crude drugs and field photos.
Foreword -- Preface -- Abbreviations -- Plant names - Sanskrit name-Tamil name
Includes field photos
Keywords: Medicinal Plants -- Western Ghat-Agasthyamalai; Herbal Wealth; Herbaria -- Guide